Hepatic Surgery - Abdeldayem, Hesham (IntechOpen, 2013)
Longmire, called it a "hostile" organ because it welcomes malignant cells and sepsis so warmly, bleeds so copiously, and is often the ?rst organ to be injured in blunt abdominal trauma. To balance these negative factors, the liver has two great attributes: its ability to regenerate after massive loss of substance, and its ability, in many cases, to forgive insult. This book covers a wide spectrum of topics including, history of liver surgery, surgical anatomy of the liver, techniques of liver resection, benign and malignant liver tumors, portal hypertension, and liver trauma. Some important topics were covered in more than one chapter like liver trauma, portal hypertension and pediatric liver tumors.